METHOD OF SECURE EXCHANGE AND STORAGE OF FILESIN HYBRID PEER-TO-PEER NETWORKS - KRENTSIN, MYKHAILO; KUPERSHTEIN, LEONID (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article proposes a method for secure file exchange and storage in peer-to-peer networks based on the IPFS (InterPlanetary File System) protocol and a linear feedback shift register (LFSR). The use of IPFS provides efficient decentralized data storage with guaranteed integrity due to the use of content-oriented addressing based on hash functions. In IPFS, each file or data block is identified by a unique CID (Content Identifier), which changes with any modification of the content. To increase confidentiality before uploading files to the network, it is proposed to use an encryption method based on a linear feedback shift register (LFSR) and counters. This method provides efficient generation of pseudo-random permutations of the file bytes, which makes it impossible to decrypt it without knowing the key. Encryption using the FLSR is characterized by high speed, ease of implementation, and low requirements for computing resources. This is especially important for peer-to-peer networks, where nodes may have limited performance and unstable connections. The proposed approach eliminates the vulnerability of IPFS associated with the possibility of obtaining file contents based on their CIDs, since even with the presence of an identifier, only encrypted content is available. In addition, the method ensures the confidentiality of the transmitted data, since files are transmitted in encrypted form and can only be decrypted by authorized nodes. The method also provides high performance due to the features of IPFS: files or their fragments (IPLD objects) can be downloaded in parallel from several nodes, which speeds up the transfer of large amounts of data. The method can be used in decentralized storage systems, platforms for secure file exchange, as well as in environments with increased requirements for information security.